Prevalence of and risk factors for FIV and FeLV infection in two shelters in the United Kingdom (2011-2012) - Stavisky, Jenny; Dean, Rachel S.; Molloy, Michael Henry (BMJ Publishing Group, 2017)
The aims of this study were to determine the prevalence of feline leukaemia virus (FeLV) and feline immunodeficiency virus (FIV) infections in cats presented to two RSPCA (Royal Society for the Prevention of Cruelty to Animals) animal rehoming centres and to identify risk factors for infection. All cats presented at each centre between August 2011 and August 2012 were subjected to a patient-side test for FeLV/FIV on entry. Kittens under three months and cats euthanased within a short time of presentation were excluded from the study. Univariable and multivariable logistic regression were used to separately determine risk factors for FeLV and FIV infections. At shelter A, the prevalence of FIV infection was 11.4 per cent (54/474) and FeLV infection was 3 per cent (14/473), with two FIV/FeLV coinfections identified. At shelter B, the prevalence of FIV infection was 3 per cent (4/135) and FeLV infection was 0 per cent (0/135). Cats at shelter A were significantly more likely than those at shelter B to test positive for FIV (p=0.0024) and FeLV (p=0.048). Male cats were more likely to be infected with FIV (odds ratio 27.1, p=0.001), and thin body condition and musculoskeletal disease were associated with risk of FeLV. Overall, FIV-positive and FeLV-positive cats were significantly older (median ages 5.1 and 4.75 years, respectively) than the uninfected populations (median ages 3.4 and 3.5 years, respectively). This study shows that the prevalence of these diseases varies between shelter populations. Local knowledge combined with the risk factors identified may be useful in focusing resources for population testing strategies.